Social neuroscience perspective on empathy: an electrophysiological study - Tatalović-Vorkapić, Sanja; Tadinac, Meri (2009)
By combining biological and psychological approaches, social neuroscience sheds a new light on the complex phenomenon of empathy. Therefore, it was interesting to examine whether there were any electrophysiological correlates of empathy, by analyzing the relationship between empathy and latencies/amplitudes of evoked potentials (N1, P2, N2, P3 & Sw). According to previous findings it was expected, as a neutral task had been used, that higher empathy would be significantly correlated with those components that have similar distribution on the head. A sample consisted of N=54 female psychology students, within the age range 19-23 years, all right-handers and without previous psychiatric/neurological illness. Evoked potentials were measured by using the standard visual oddball paradigm in two trials with two occipital and two parietal electrodes. Empathy was measured by the standardised version of EPQ-IVE (1). The participants were divided in two groups according to the median on Empathy subscale: Low empathy group (E≤14) and High empathy group (E>14). Correlation analysis showed a significant negative correlation between empathy and N2-amplitude in the first trial at one parietal electrode (r=-.36, p<.01). More empathetic students showed lower extraction of stimuli characteristics and target selection during visual discrimination task, probably due to a neutral task that has been used. N2-component has fronto-central distribution, partially similar to the one usually registered in participants experiencing empathy (2), which is in accordance with our expectations. A possible use of emotionally triggered tasks for evoking brain potentials in the future studies is discussed.
Projekt MZOS
ENG